A programmable self-dissolving hydrogel material and preparation method thereof

By developing a programmable autolytic hydrogel based on oxidation stimulation, the chemical reaction between the embedded stimulation reagent and the crosslinking agent is solved, and the effect of autonomous degradation rate of the existing hydrogel is achieved at ambient temperature and the effect of autonomous degradation and precise control of the autolysis time is achieved.

CN119241767BActive Publication Date: 2025-04-11ZHEJIANG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411766688.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-11
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing active degradation hydrogels have problems such as difficult to control the degradation rate, unevenness and strict environmental conditions, which affect their practical application in the fields of biomedical and flexible electronics.

Method used

Bionic cells are subject to gene autoapoptotic phenomenon, and a programmable autolysis hydrogel based on oxidation stimulation is developed. It can undergo a controllable chemical reaction between pre-embedded stimulation reagents and crosslinking agents to achieve autonomous degradation at ambient temperature, and precisely control the autolysis time by adjusting parameters such as crosslinking agent ratio and monomer type.

Benefits of technology

It realizes that the hydrogel self-dissolves and degrades at ambient temperature without the need for external stimulation, avoids the damage caused by stimulation factors to the body, and can be permanently preserved at low temperatures, providing more accurate, fast and uniform degradation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241767B_ABST
    Figure CN119241767B_ABST
Patent Text Reader

Abstract

The present invention discloses a programmable self-dissolving hydrogel material and a preparation method thereof, and belongs to the field of new materials. The preparation method disclosed in the present invention dissolves a hydrogel monomer, a cross-linking agent, a photoinitiator and a pre-embedded stimulation reagent in a solvent to obtain a hydrogel precursor, and obtains a hydrogel material after photocuring. The hydrogel material realizes a phase change behavior from solid self-dissolution to liquid at room temperature. The self-dissolution of the present invention is based on an oxidation reaction between the pre-embedded stimulation reagent and the cross-linking agent. The self-dissolution time of the hydrogel can be programmed by adjusting parameters such as the type and ratio of the cross-linking agent, the type and ratio of the monomer, the ratio of the pre-embedded stimulation reagent, and the ratio of the solvent, so as to realize rapid, controllable and timed degradation. The hydrogel material of the present invention can realize the functions of not losing water at room temperature and not freezing at low temperature, which is of great significance for the shape transformation of hydrogels without external stimulation, minimally invasive surgery and physically inaccessible systems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of new materials, and in particular to a programmable self-dissolving hydrogel and a preparation method thereof. Background Art

[0002] Hydrogels are widely used in biomedicine, flexible electronics, industry and agriculture due to their unique physical and chemical properties, such as high water content, good biocompatibility, adjustable mechanical properties and environmental responsiveness. By introducing degradability, that is, the hydrogel can be decomposed into small molecules under specific conditions (such as temperature, pH value changes or enzyme action), it has unique advantages in certain application scenarios. For example, hydrogels can be used as wound adhesives and are naturally absorbed or excreted by the human body after completing specific functions, reducing the need for secondary surgery and potential risks. Hydrogels used for oil pollution cleanup can degrade under the action of seawater or sunlight after absorbing oil pollution, reducing the impact on marine ecology.

[0003] At present, the degradation methods of hydrogels are mainly concentrated in passive degradation methods, such as light stimulation, pH stimulation, ultrasound stimulation, thermal stimulation and magnetic stimulation. However, these hydrogels that rely on external stimulation are often sensitive to environmental conditions, which increases the difficulty of control in practical applications. For example, when pH-stimulated degradable hydrogels are used in different parts of the human body, due to the differences in pH values, the degradation behavior may be unpredictable, thereby affecting the therapeutic effect. In addition, some stimulus-responsive hydrogels may only be suitable for specific medical conditions or environments. For example, the application of photosensitive hydrogels in the body is limited by the depth of light penetration and may not be suitable for the treatment of deep tissues.

[0004] Compared with passive degradation behavior, active degradation emphasizes that hydrogels can degrade autonomously without external stimulation signals. The main active degradation methods are hydrolysis and autocatalytic enzyme reactions, which solve the problem that passive degradation is limited by stimulation conditions. However, the existing active degradation methods still have problems such as slow degradation rate, difficulty in precise control, and uneven degradation, which affect their performance in practical applications. In addition, these actively degradable hydrogels are also very demanding on environmental conditions during transportation and storage. Therefore, the research and development of controllable actively degradable multifunctional hydrogels suitable for biomedicine, flexible electronics and other fields is still extremely challenging and requires the development of new strategies. These strategies may include improving the chemical structure of hydrogels, introducing new degradation mechanisms, or developing more effective preparation methods to achieve more precise, faster and more uniform degradation performance. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, mainly aiming at the problem that the active degradation rate is difficult to control, the present invention provides a programmable autolytic hydrogel based on oxidative stimulation and a preparation method thereof, which can not only ensure that the hydrogel does not lose water and self-degrades at a fixed time at ambient temperature, but also can be stored for a long time and maintain the self-degradation performance of the hydrogel for a long time.

[0006] The specific technical solutions adopted by the present invention are as follows:

[0007] In the first aspect, the present invention provides a method for preparing a programmable self-dissolving hydrogel material, wherein a hydrogel precursor is formed by mixing a hydrogel monomer, a photoinitiator, a cross-linking agent, a pre-embedded stimulation reagent and a solvent, and the hydrogel precursor is photocured to obtain a hydrogel material capable of spontaneous degradability; the cross-linking agent is a diselenide bond-based cross-linking agent or a thioketal-based cross-linking agent, and the pre-embedded stimulation reagent is ammonium persulfate or potassium persulfate.

[0008] As a preferred embodiment of the first aspect, the cross-linking agent is a diselenide bond-based cross-linking agent, and the structural formula is: .

[0009] As a preferred embodiment of the first aspect, the cross-linking agent is a thioketal-based cross-linking agent having the structural formula: .

[0010] As a preferred embodiment of the first aspect, the hydrogel monomer is at least one of acrylamide, acrylic acid, and N-isopropylacrylamide, and the molar ratio of the crosslinking agent to the hydrogel monomer is 1:(100-300).

[0011] As a preferred embodiment of the first aspect, the photoinitiator is at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP), diphenyl-(2,4,6-trimethylbenzoyl) phosphine oxide, and dibenzoyl peroxide, and the molar ratio of the photoinitiator to the hydrogel monomer is 1: (100~400).

[0012] As a preferred embodiment of the first aspect, the molar ratio of the pre-embedded stimulation reagent to the hydrogel monomer is 1:(40-450).

[0013] As a preferred embodiment of the first aspect, the solvent is a chitosan aqueous solution, water, or a mixed solvent of water and glycerol, and the solvent accounts for 80 wt.% to 95 wt.% of the hydrogel precursor.

[0014] As a preference in the above first aspect, the solvent is a mixed solvent of water and glycerol.

[0015] As a preferred embodiment of the first aspect, the photocuring method is: placing the hydrogel precursor liquid in a mold under 365 nm ultraviolet light for 60 to 300 s to cure it into a hydrogel material, or using photocuring 3D printing technology to print it into a three-dimensional structure.

[0016] In a second aspect, the present invention provides a method for preparing a programmable self-dissolving hydrogel material, wherein the method uses hydrogel monomers, photoinitiators, crosslinkers, pre-embedded stimulating agents and solvents as raw materials for mixing to form a hydrogel precursor, and uses the type of crosslinker, the proportion of the crosslinker in the hydrogel precursor, the type of hydrogel monomers, the proportion of the hydrogel monomers in the hydrogel precursor, the proportion of the pre-embedded stimulating agents in the hydrogel precursor, and the proportion of the solvent in the hydrogel precursor as parameter variables for regulating the degradation rate of the hydrogel, and constructs different parameter variable combinations and hydrogel degradation methods in advance using measured data. A mapping relationship between the autodissolution time of a gel material; when preparing a hydrogel material with a target autodissolution time, the mapping relationship is used to find a parameter variable combination whose autodissolution time satisfies the target value, and then a hydrogel monomer, a photoinitiator, a cross-linking agent, a pre-embedded stimulation reagent and a solvent that satisfy the parameter variable combination are mixed to form a hydrogel precursor, and the obtained hydrogel precursor is photocured to obtain a hydrogel material capable of spontaneous degradation; the cross-linking agent is a diselenide bond-based cross-linking agent or a thioacetal-based cross-linking agent, and the pre-embedded stimulation reagent is ammonium persulfate or potassium persulfate.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] Compared with the prior art, the present invention provides a programmable self-dissolving hydrogel based on oxidative stimulation and a preparation method thereof, designs and synthesizes a fast or slow oxidative stimulation self-degrading crosslinker, specifically selects a mode of polymerization followed by degradation, and regulates the hydrogel manufacturing method (mold method or 3D printing), degradation speed, water retention and preservation capacity by adjusting the crosslinker ratio, monomer type and ratio, pre-embedded stimulation reagent ratio, solvent ratio and other parameters. The hydrogel realizes self-dissolution at ambient temperature without any external stimulation. The essence of degradation lies in the controllable chemical reaction between the pre-embedded stimulation reagent and the crosslinker, the breakage of the diselenide bond or thioketal bond in the crosslinker, and the reduction of the crosslinking degree of the hydrogel network, which ultimately makes the hydrogel unable to maintain a three-dimensional form and undergoes a transition from solid to liquid. Compared with the passive stimulation degradation method, the hydrogel of the present invention can realize self-degradation without any stimulation method, avoiding the damage of the stimulation factor to the body, and can realize self-degradation at the site where the stimulation factor cannot be implemented, providing a far-reaching reference for active degradation of hydrogel. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The structural formula of the diselenide bond crosslinking agent synthesized in Example 1 is1 H NMR spectrum.

[0020] Figure 2 This is a graph showing the change in mechanical properties when 20 μl of 10% APS is added to the hydrogel in Example 1 (37°C).

[0021] Figure 3 This is a graph showing the change in mechanical properties when 60 μl of 10% APS is added to the hydrogel in Example 2 (37°C).

[0022] Figure 4 This is a graph showing the change in mechanical properties when 100 μl of 10% APS is added to the hydrogel in Example 3 (37°C).

[0023] Figure 5 This is a graph comparing the changes in mechanical properties of polyacrylamide hydrogel before and after heat treatment for 6 h without adding APS in Experiment 1 (37°C).

[0024] Figure 6 The comparison experiment 2 used only thermal initiator and cross-linker to react for 2 h before and after the monomer (or chain) in the solution 1 HNMR spectrum.

[0025] Figure 7 This is a graph showing the changes in mechanical properties of the hydrogel after degradation for 3 h in Example 5.

[0026] Figure 8 This is a graph showing the change in mechanical properties of the hydrogel after degradation for 3 h in Example 6.

[0027] Fig. 9 The structural formula of the thioketal bond crosslinking agent synthesized in Example 7 is 1 H NMR spectrum.

[0028] Fig.10 This is a graph showing the change in mechanical properties after adding different amounts of 10% APS (20, 60, 100 μl) to the TKA cross-linked autolytic hydrogel in Example 7 and degrading it for 48 hours.

[0029] Fig.11 This is a live or dead staining image of the solution conditioned medium after the degradation of the autolytic hydrogel in Example 8 and the complete medium (control group) after culturing NIH3T3 mouse embryonic fibroblasts for 24 hours. DETAILED DESCRIPTION

[0030] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific implementation mode of the present invention is described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below. The technical features in each embodiment of the present invention can be combined accordingly without conflicting with each other.

[0031] The present invention provides a method for preparing a programmable self-dissolving hydrogel material, which is specifically as follows: a hydrogel precursor is formed by mixing a hydrogel monomer, a photoinitiator, a cross-linking agent, a pre-embedded stimulation reagent and a solvent, and the hydrogel precursor is photocured to obtain a hydrogel material capable of spontaneous degradation.

[0032] The crosslinking agent used in the present invention needs to be an oxidatively stimulated degradable crosslinking agent, that is, a crosslinking agent that can be degraded by the oxidative stimulation of the pre-embedded stimulating agent. Oxidatively stimulated degradable crosslinking agents are divided into fast-degradable crosslinking agents and slow-degradable crosslinking agents according to the speed of degradation. Fast-degradable crosslinking agents are based on diselenide bonds ( ) crosslinker, the slow degradation crosslinker is based on thioketal ( ) crosslinker. Fast or slow degradation The degradation rate of the crosslinker is derived from the bond energy between atoms, which is 172 kJ / mol for a diselenide bond and 272 kJ / mol for a carbon-sulfur bond.

[0033] The above-mentioned fast degradation crosslinking agent is prepared by reacting selenocystamine dihydrochloride and a monomer with a functional double bond, wherein the monomer with a functional double bond includes acrylic acid and acryloyl chloride, and the molar ratio of selenocystamine dihydrochloride to the monomer with a functional double bond is 1:1-3. In the embodiment of the present invention, the fast degradation crosslinking agent that can be used is based on a diselenide bond ( ) has the following cross-linking agent structure: , referred to as SOA.

[0034] The synthesis of the above slow degradation crosslinking agent is similar to the above, and is prepared by reacting 2,2'-(propane-2,2-diylbis(sulfonamide))diethylamine and a monomer with a functional double bond. The type of the monomer with a functional double bond includes acrylic acid or acryloyl chloride, and the molar ratio of 2,2'-(propane-2,2-diylbis(sulfonamide))diethylamine to the monomer with a functional double bond is 1:1-3. In the embodiment of the present invention, the slow degradation crosslinking agent that can be used is based on thioketal ( ) has the following cross-linking agent structure: , referred to as TKA.

[0035] The principle of the hydrogel material prepared in the present invention being able to self-dissolve (i.e., spontaneously degrade) is that the pre-embedded stimulating agent and the cross-linking agent undergo a controllable chemical reaction, the diselenide bond or thioketal bond in the cross-linking agent is broken, and the cross-linking degree of the hydrogel network is reduced, which ultimately makes the hydrogel unable to maintain a three-dimensional form and undergoes a transition from a solid state to a liquid state. Therefore, based on this mechanism, as long as the combination of the pre-embedded stimulating agent and the cross-linking agent is appropriately selected, the hydrogel can achieve self-dissolution at ambient temperature without any external stimulation.

[0036] In addition, except for the core component cross-linking agent and pre-embedded stimulation reagent that realize the self-dissolution of the hydrogel material, which need to be strictly limited, the remaining hydrogel precursor raw materials can theoretically be configured according to the conventional hydrogel preparation method.

[0037] In an embodiment of the present invention, the selection and proportion of the remaining hydrogel precursor raw materials are preferably as follows:

[0038] The hydrogel monomer is at least one of acrylamide, acrylic acid, and N-isopropylacrylamide, and the molar ratio of the crosslinking agent to the hydrogel monomer is 1:(100-300).

[0039] The photoinitiator is at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP), diphenyl-(2,4,6-trimethylbenzoyl) phosphine oxide, and dibenzoyl peroxide, and the molar ratio of the photoinitiator to the hydrogel monomer is 1: (100-400).

[0040] The above-mentioned pre-embedded stimulating agent is an oxidative stimulating chemical monomer, including ammonium persulfate or potassium persulfate. The molar ratio of the pre-embedded stimulating agent to the hydrogel monomer is 1:(40-450).

[0041] The above-mentioned solvent is a chitosan aqueous solution, water or a mixed solvent of water and glycerol, and the mass ratio of the solvent to the hydrogel precursor is 80 wt.%~95 wt.%. The above-mentioned solvent is preferably a mixed solvent of water and glycerol, and the volume ratio of water to glycerol is preferably 1:(0-0.8). The volume ratio of water to glycerol is further preferably 2:3. The hydrogel with this preferred ratio can further improve the long-lasting performance of the hydrogel material at low temperatures, and the degradation of the pre-embedded stimulation reagent at low temperatures is inhibited. When placed at -20°C, the hydrogel can basically be permanently preserved.

[0042] In addition, it should be noted that the above-mentioned hydrogel precursor is prepared into a hydrogel material by photocuring, and the specific form of photocuring can be various, and can be realized by mold method or 3D printing. In an embodiment of the present invention, the hydrogel precursor liquid can be placed in a mold under 365 nm ultraviolet light for 60 to 300 s, thereby curing into a hydrogel material corresponding to the shape of the mold, or it can also be printed into a more complex three-dimensional structure using photocuring 3D printing technology.

[0043] The hydrogel material prepared in the present invention can degrade spontaneously without any stimulation, and the time of autolysis can be programmably controlled based on oxidative stimulation, and the autolysis time can be controlled within 0.5-168 hours. Even by using a mixed solvent of water and glycerol, it can be controlled not to degrade at all, and the chemical reaction between molecules can be inhibited at a low temperature of -20°C, playing a role of permanent preservation.

[0044] In the embodiments of the present invention, it is found that a series of components mixed to form a hydrogel precursor, such as a hydrogel monomer, a photoinitiator, a cross-linking agent, a pre-embedded stimulating agent, and a solvent, will affect the final autolysis time. Therefore, the present invention can programmably and accurately or fuzzily control the autolysis time of the final prepared hydrogel based on the selection of the types of these components and the regulation of the ratios between them.

[0045] Based on the characteristics of programmable autolysis time, the hydrogel prepared by the present invention can be used in various fields such as hydrogel dressings, targeted drug release and nanorobot cluster transportation. The hydrogel material of the present invention can achieve the functions of not losing water at room temperature and not freezing at low temperature, which is of great significance for hydrogel shape transformation without external stimulation, minimally invasive surgery and physically inaccessible systems.

[0046] In order to better demonstrate the specific preparation method and hydrogel performance of the programmable self-dissolving hydrogel in the present invention, a number of examples are given below. The reagents used in these examples, unless otherwise specified, can all be existing commercially available products.

[0047] Example 1

[0048] In this embodiment, a programmable self-dissolving hydrogel is prepared, and the preparation method includes the following steps:

[0049] Step (1), synthesis of a diselenide crosslinker: 0.5 g of selenocystamine dihydrochloride and 3 molar equivalents (based on the molar amount of 0.5 g of selenocystamine dihydrochloride) of acrylic acid were added to a mixed solution of 1 ml of water and 5 ml of dimethylformamide, and then 6 molar equivalents (based on the molar amount of 0.5 g of selenocystamine dihydrochloride) of N,N-diisopropylethylamine were added. After stirring at room temperature for 30 min, the solvent was removed under reduced pressure, and the product was purified by column chromatography using a developing solvent of dichloromethane:methanol = 20:1 (volume ratio). After the eluent was evaporated to remove the solvent, a diselenide crosslinker SOA was obtained, which was dissolved in dimethyl sulfoxide (DMSO) and used at a concentration of 24 mg / 100 μl. 1 H NMR Figure 1 As shown, its structural formula is: .

[0050] Step (2), preparation of programmable self-dissolving hydrogel: add 1.42 g acrylamide monomer into 5 ml water and stir evenly, then add 200 μl 2.5% LAP solution and 25 μl DMSO solution containing SOA crosslinker (SOA concentration 24 mg / 100 μl) in sequence and mix evenly, finally add 20 μl 10% ammonium persulfate (APS) solution (concentration marked as A), and ultrasonically vibrate to evenly form a hydrogel precursor, and then irradiate under 365 nm ultraviolet light for 90 s to obtain a hydrogel material.

[0051] Step (3), placing the hydrogel material in a 37°C constant temperature box, and testing the changes in its mechanical properties every 2 hours. Figure 2 As shown, since the mass of ammonium persulfate is less than the mass of the cross-linker, although part of the SOA cross-linker is destroyed by the pre-embedded APS and the bonds are broken, resulting in a decrease in the final hydrogel mechanical properties, there is still a partial cross-linked network, and the overall shape of the hydrogel remains unchanged without complete autolysis.

[0052] Example 2

[0053] The programmable self-dissolving hydrogel was prepared according to step (1) and step (2) in Example 1, except that the 20 μl 10% ammonium persulfate (APS) solution added in Example 1 was replaced with 60 μl 10% APS solution (concentration marked as B). The prepared hydrogel material was placed in a 37°C incubator and its mechanical properties were tested every 1 h. The self-degradation behavior was determined by the fluidity of the hydrogel in an inverted reagent bottle. Figure 3 As shown, the mechanical properties of the hydrogel prepared in this example dropped significantly after 5 hours, and then a phase transition occurred, that is, a self-dissolution phenomenon from solid to liquid occurred.

[0054] Example 3

[0055] The programmable self-dissolving hydrogel was prepared according to step (1) and step (2) in Example 1, except that the 20 μl 10% ammonium persulfate (APS) solution added in Example 1 was replaced with 100 μl 10% APS solution (concentration marked as C). The prepared hydrogel material was placed in a 37°C incubator and its mechanical properties were tested every 0.5 h. The self-degradation behavior was determined by the fluidity of the hydrogel in an inverted reagent bottle. Figure 4 As shown, the mechanical properties of the hydrogel prepared in this example dropped significantly after 2 hours, and then a phase transition from solid to liquid occurred. APS solutions of different concentrations were added in Examples 1 to 3, and the comparison of the results showed that the hydrogel prepared in the present invention has adjustable self-degradation rate behavior, and different APS ratios can change the autolysis time.

[0056] Comparative Example

[0057] Generally, APS is used as a free radical initiator in the hydrogel synthesis process to initiate the gelation of hydrogel, but the role of APS in the hydrogel precursor of the present invention is to pre-embed the stimulating reagent, which is used to react with the cross-linking agent to promote the bond breaking of the cross-linking agent, and it does not act as an initiator. In order to verify that the APS in the hydrogel precursor of the present invention has a chemical reaction with the cross-linking agent, and to prove that the reaction rate of APS with the cross-linking agent is greater than the polymerization rate of the monomer initiated by APS, the following comparative experiments were conducted:

[0058] Comparative experiment 1: Add 1.42 g acrylamide monomer to 5 ml water and stir evenly, then add 200 μl 2.5% LAP solution and 25 μl DMSO solution containing SOA crosslinker in turn and mix evenly, ultrasonically vibrate to form a hydrogel precursor, and irradiate under 365 nm UV light for 90 s to obtain a hydrogel. Place the above hydrogel in a 37 ℃ constant temperature box and test the changes in its mechanical properties every 6 hours. Figure 5 As shown, without the addition of APS, heat does not cause changes in the mechanical properties of the hydrogel, indicating that APS reacts chemically with the cross-linker.

[0059] Comparative experiment 2: 1.42 g acrylamide monomer was added to 5 ml water and stirred evenly, then 25 μl DMSO solution containing SOA crosslinker was added and mixed evenly, and finally 60 μl 10% ammonium persulfate (APS) solution (concentration marked as B) was added, and ultrasonic vibration was used to evenly form a hydrogel precursor, and thermally cured at 60°C for 2 hours to obtain a hydrogel. After 2 hours, the hydrogel did not solidify and remained liquid. Figure 6 1The H NMR spectrum test of the monomer components in the solution showed that after the addition of APS and the crosslinking agent, the acrylamide monomer did not polymerize, thus proving that the reaction rate of APS and the crosslinking agent in the hydrogel precursor of the present invention was greater than the polymerization rate of the monomer initiated by APS.

[0060] Example 4

[0061] In this embodiment, a diselenide bond crosslinker SOA was prepared according to step (1) in embodiment 1, and then a programmable self-dissolving hydrogel was prepared according to the following process: 1.42 g of acrylamide monomer was added to a mixed solution consisting of 2 ml of water and 3 ml of glycerol and stirred evenly, and then 200 μl of 2.5% LAP solution and 25 μl of DMSO solution containing SOA crosslinker (wherein the SOA concentration was 24 mg / 100 μl) were added in sequence and mixed evenly, and finally 100 μl of 10% APS solution was added, and ultrasonic vibration was performed to uniformly form a hydrogel precursor, and then irradiated under a 365 nm ultraviolet lamp for 90 s to obtain a hydrogel material, and the self-degradation process was recorded at room temperature. The phenomenon in the degradation process is as follows: at room temperature, the mixed solution gel did not lose water, the gel began to self-degrade after 2.5 hours, and the gel was completely degraded after 4 hours and became a flowable liquid.

[0062] In addition, the properties of the hydrogel material prepared in this embodiment at low temperatures were studied. The results showed that glycerol molecules can interfere with the hydrogen bond network between water molecules. When glycerol is mixed with water, it can lower the freezing point of water, so that water molecules remain liquid at lower temperatures instead of forming solid ice crystals. When the hydrogel prepared in this embodiment is placed at -20°C, the hydrogel not only maintains transparency and stretchability, but also the pre-embedded stimulation reagent is inhibited from decomposing the cross-linking agent at low temperatures, making it difficult to react chemically with the cross-linking agent, so that the hydrogel can be permanently preserved at low temperatures.

[0063] Example 5

[0064] In this embodiment, the diselenide bond crosslinker SOA was prepared according to step (1) in embodiment 1, and then the programmable self-dissolving hydrogel was prepared according to the following process: 200 μl of 2.5% LAP solution and 25 μl of DMSO solution containing SOA crosslinker (wherein the SOA concentration was 24 mg / 100 μl) were added to 30% acrylic acid aqueous solution in sequence and mixed evenly, and finally 40 μl of 10% APS solution was added, ultrasonically vibrated to evenly form a hydrogel precursor, and then irradiated under 365 nm ultraviolet light for 90 s to obtain a hydrogel material. The above hydrogel material was placed in a 37°C constant temperature box, and the changes in its mechanical properties were tested every 3 h, such as Figure 7 As shown, it indicates that the mechanical properties of the above hydrogels have changed significantly.

[0065] Example 6

[0066] In this embodiment, the diselenide bond crosslinker SOA was prepared according to step (1) in Example 1, and then a programmable self-dissolving hydrogel was prepared according to the following process: 1.42 g of acrylamide monomer was added to 5 ml of a 0.4 wt.% chitosan aqueous solution and stirred evenly, and then 200 μl of a 2.5% LAP solution and 25 μl of a DMSO solution containing an SOA crosslinker (wherein the SOA concentration was 24 mg / 100 μl) were added in sequence and mixed evenly, and finally 60 μl of a 10% APS solution (concentration marked as B) was added, and ultrasonic vibration was performed to uniformly form a hydrogel precursor, and then irradiated under a 365 nm ultraviolet lamp for 90 s to obtain a hydrogel material. The difference between this embodiment and Example 2 is only that the solvents of the precursors are different, and chitosan and acrylamide are introduced at the same time to make the prepared hydrogel a double network hydrogel. The above hydrogel material was placed in a 37°C constant temperature box, and the changes in its mechanical properties were tested every 3 h, as shown in FIG. Figure 8 As shown in the figure, the mechanical properties of the above hydrogel decreased significantly after 3 h.

[0067] Example 7

[0068] In this embodiment, a programmable self-dissolving hydrogel is prepared, and the preparation method includes the following steps:

[0069] (1) Synthesis of thioketal crosslinker: Weigh 0.2 g of 2,2'-(propane-2,2-diylbis(sulfonamide))diethylamine in a beaker and add dichloromethane to dissolve it. Add 3 molar equivalents (based on the molar amount of 0.2 g 2,2'-(propane-2,2-diylbis(sulfonamide))diethylamine) of N,N-diisopropylethylamine, and then slowly dropwise add 2 molar equivalents (based on the molar amount of 0.2 g 2,2'-(propane-2,2-diylbis(sulfonamide))diethylamine) of acryloyl chloride in an ice bath. React at room temperature for 30 min. After the reaction is completed, the reaction solution is concentrated under reduced pressure and purified by column chromatography with dichloromethane:methanol = 10:1 (volume ratio) to obtain the thioketal crosslinker TKA, which is dissolved in DMSO and used at a concentration of 20 mg / 100 μl. The obtained product TKA 1 H NMR Fig. 9 As shown, its structural formula is: .

[0070] (2) Preparation of programmable self-dissolving hydrogel: 1.42 g acrylamide monomer was added to 5 ml water and stirred evenly. Then, 200 μl 2.5% LAP solution and 25 μl DMSO solution containing TKA crosslinker (TKA concentration: 20 mg / 100 μl) were added in sequence and mixed evenly. Finally, the mixture was divided into three groups and three different amounts of APS solution were added to each group. Group A was added with 20 μl 10% APS solution, Group B was added with 60 μl 10% APS solution, and Group C was added with 100 μl 10% APS solution. Ultrasonic vibration was used to uniformly form a hydrogel precursor, which was then irradiated under 365 nm UV light for 90 s to obtain a hydrogel material.

[0071] (3) The hydrogel material was placed in a 37°C constant temperature box and its mechanical properties were tested every 48 hours. Fig.10 As shown in the figure, it can be seen that the mechanical properties of the hydrogels decreased after 48 h, and the degree of mechanical decline was affected by the APS content. Therefore, the hydrogel prepared based on the thioketal crosslinker TKA in this embodiment has a slower self-degradation rate than the hydrogel prepared based on the diselenide bond crosslinker SOA, which is derived from the larger bond energy of the CS bond.

[0072] Therefore, the diselenide bond crosslinker SOA can be used as a fast-degrading crosslinker, while the thioketal crosslinker TKA can be used as a slow-degrading crosslinker. The specific selection can be based on the actual desired control of the hydrogel autolysis time.

[0073] Example 8

[0074] In this embodiment, the cytotoxicity of the hydrogel solution material after the autolytic hydrogel degradation was tested, and the process was as follows:

[0075] (1) According to step (1) in Example 1, a diselenide bond crosslinker SOA was prepared, and then a programmable self-dissolving hydrogel was prepared according to the following process: 1.42 g of acrylamide monomer was added to 5 ml of water and stirred evenly, and then 200 μl of 2.5% LAP solution and 25 μl of DMSO solution containing SOA crosslinker (wherein the SOA concentration was 24 mg / 100 μl) were added in sequence and mixed evenly, and finally 60 μl of 10% APS solution was added, and ultrasonic vibration was performed to uniformly form a hydrogel precursor, and then irradiated under a 365 nm ultraviolet lamp for 90 s to obtain a hydrogel material. The hydrogel was placed at 37°C and self-degraded into macromolecular chains.

[0076] (2) The hydrogel material was subjected to a cytotoxicity test on NIH3T3 mouse embryonic fibroblasts. The experimental method was as follows: NIH3T3 cells were seeded in a 96-well plate (10 4Cells were then treated with conditioned medium containing 20 mg of the degradation solution per ml. The cells were incubated at 37 °C and 5% CO2 for 24 h. The cytotoxicity was qualitatively assessed using the Calcein AM / PI staining kit; fluorescence images of the cultured cells were captured using an inverted fluorescence microscope at excitation / emission wavelengths of 490 / 515 nm and 535 / 617 nm.

[0077] The results of this example are as follows Fig.11 As shown, the hydrogel has good biocompatibility, and after 24 h of co-culture with cells, the cells have a relatively high survival rate, indicating that the hydrogel has great application prospects in emergency hemostasis.

[0078] Example 9

[0079] Based on the above embodiments, it can be seen that the present invention provides different programmable self-dissolving hydrogels and preparation methods thereof. The results of each embodiment show that the self-dissolution of the hydrogel of the present invention is based on the oxidation reaction between the pre-embedded stimulation reagent and the cross-linking agent. Therefore, by adjusting the type and ratio of the cross-linking agent, the type and ratio of the monomer, the ratio of the pre-embedded stimulation reagent, the ratio of the solvent and other parameters, the self-dissolution time of the hydrogel can be programmed to achieve rapid, controllable and timed degradation. Therefore, in this embodiment, a method for preparing a programmable self-dissolving hydrogel material is further provided, and its specific method is as follows:

[0080] The hydrogel monomer, photoinitiator, crosslinker, pre-embedded stimulating agent and solvent are used as raw materials to mix and form a hydrogel precursor, and the type of crosslinker, the proportion of crosslinker in the hydrogel precursor, the type of hydrogel monomer, the proportion of hydrogel monomer in the hydrogel precursor, the proportion of pre-embedded stimulating agent in the hydrogel precursor, and the proportion of solvent in the hydrogel precursor are used as parameter variables to regulate the degradation rate of the hydrogel, and the mapping relationship between different parameter variable combinations and the autolysis time of the hydrogel material is constructed in advance using measured data; when preparing a hydrogel material with a target autolysis time, the parameter variable combination that satisfies the target autolysis time is found through the mapping relationship, and then the hydrogel monomer, photoinitiator, crosslinker, pre-embedded stimulating agent and solvent that meet the parameter variable combination are mixed to form a hydrogel precursor, and the obtained hydrogel precursor is subjected to light curing to obtain a hydrogel material that can be degraded spontaneously. Among them, the crosslinker needs to select a crosslinker based on a diselenide bond or a crosslinker based on thioketal, and the pre-embedded stimulating agent needs to select ammonium persulfate or potassium persulfate. The remaining hydrogel precursor raw materials can theoretically be prepared according to conventional hydrogel preparation methods, and reference can also be made to the preferred selection and preferred ratio of the hydrogel precursor raw materials described above.

[0081] It should be noted that the mapping relationship between the above-mentioned different parameter variable combinations and the autolysis time of the hydrogel material can be pre-constructed through measured data. In actual implementation, the type of cross-linking agent, the proportion of cross-linking agent in the hydrogel precursor, the type of hydrogel monomer, the proportion of hydrogel monomer in the hydrogel precursor, the proportion of pre-embedded stimulation reagent in the hydrogel precursor, and the proportion of solvent in the hydrogel precursor. At the same time, these 8 parameter variables can all sample a series of values ​​within their respective selection and proportion ranges, and then form a combination of 8 parameter variables composed of different sampling values. Based on each parameter variable combination, the corresponding hydrogel material is prepared, and its autolysis time is measured, so that the mapping relationship between different parameter variable combinations and the autolysis time of the hydrogel can be formed in a tabular form. In this embodiment, by summarizing the above-mentioned embodiments and other experimental results, a mapping relationship table as shown in Table 1 was established (wherein the type and content of the photoinitiator in each parameter variable combination are fixed to: 200 μl 2.5% LAP solution). Table 1 can be used to find the relationship between the programmable autolysis time and each parameter. By adjusting the various parameter variable combinations, a suitable hydrogel formula can be selected between 0.5 h and 168 h as required.

[0082] Table 1 Programming the hydrogel autolysis time by adjusting the precursor parameters

[0083] Hydrogel monomer Crosslinking agent Pre-embedded stimulation reagent Solvents Autolysis time Acrylamide 1.42 g SOA 6 mg 10% APS 20 μl Water 5 ml No autolysis Acrylamide 1.42 g SOA 6 mg 10% APS 40 μl Water 5 ml 24 h Acrylamide 1.42 g SOA 6 mg 10% APS 60 μl Water 5 ml 6 h Acrylamide 1.42 g SOA 6 mg 10% APS 100 μl Water 5 ml 2 h Acrylamide 1.42 g SOA 6 mg 10% APS 140 μl Water 5 ml 1 h Acrylamide 1.42 g SOA 6 mg 10% APS 180 μl Water 5 ml 0.6 h Acrylamide 0.71 g SOA 6 mg 10% APS 60 μl Water 5 ml 2 h Acrylamide 0.915 g SOA 6 mg 10% APS 60 μl Water 5 ml 4 h Acrylamide 2.13 g SOA 6 mg 10% APS 60 μl Water 5 ml 11 h Acrylamide 1.525 g SOA 6 mg 10% APS 60 μl Water 5 ml 72 h Acrylamide 1.42 g SOA 3 mg 10% APS 60 μl Water 5 ml 2 h Acrylamide 1.42 g SOA 9 mg 10% APS 60 μl Water 5 ml 18 h Acrylic acid 1.5 g SOA 6 mg 10% APS 60 μl Water 3.5 ml 6 h Acrylamide 1.42 g SOA 6 mg 10% APS 60 μl 0.4 wt.% chitosan aqueous solution 6 h Acrylamide 1.42 g SOA 6 mg 10% APS 20 μl 2 ml water: 3 ml glycerol No autolysis Acrylamide 1.42 g SOA 6 mg 10% APS 60 μl 2 ml water: 3 ml glycerol 7 h Acrylamide 1.42 g SOA 6 mg 10% APS 100 μl 2 ml water: 3 ml glycerol 1.5 h Acrylamide 0.71 g SOA 6 mg 10% APS 20 μl 2 ml water: 3 ml glycerol No autolysis Acrylamide 0.71 g SOA 6 mg 10% APS 60 μl 2 ml water: 3 ml glycerol 1.5 h Acrylamide 0.71 g SOA 6 mg 10% APS 100 μl 2 ml water: 3 ml glycerol 0.5 h Acrylamide 1.42 g TKA 4 mg 10% APS 60 μl Water 5 ml 168 h Acrylamide 1.42 g TKA 4 mg 10% APS 100 μl Water 5 ml 88 h Acrylamide 1.42 g TKA 2 mg + SOA 3 mg 10% APS 60 μl Water 5 ml 60 h

[0084] Of course, the above Table 1 shows only an exemplary mapping relationship. In practical applications, the hydrogel autolysis time under more parameter variable combinations can be further measured to further improve the precision of the mapping relationship. At the same time, in addition to the mapping relationship in the form of a table, if there is enough data, other forms of mapping relationships can also be constructed through relationship curve models, machine learning models, etc., and there is no restriction on this.

[0085] The above-described embodiments are only some preferred implementations of the present invention, but are not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A method for preparing a programmable self-dissolving hydrogel material, characterized in that: A hydrogel precursor is formed by mixing a hydrogel monomer, a photoinitiator, a crosslinker, a pre-embedded stimulating agent and a solvent, and the hydrogel precursor is photocured to obtain a hydrogel material capable of spontaneous degradation; the crosslinker is a thioketal-based crosslinker, and the pre-embedded stimulating agent is ammonium persulfate or potassium persulfate; The cross-linking agent based on thioketal has the structural formula: ; The hydrogel monomer is at least one of acrylamide, acrylic acid, and N-isopropylacrylamide, and the molar ratio of the crosslinking agent to the hydrogel monomer is 1:(100-300); The photoinitiator is at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, diphenyl-(2,4,6-trimethylbenzoyl) phosphine oxide, and dibenzoyl peroxide, and the molar ratio of the photoinitiator to the hydrogel monomer is 1: (100-400); The molar ratio of the pre-embedded stimulation reagent to the hydrogel monomer is 1:(40-450); The solvent is a chitosan aqueous solution, water, or a mixed solvent of water and glycerol, and the solvent accounts for 80 wt.% to 95 wt.% of the hydrogel precursor.

2. The method for preparing a programmable self-dissolving hydrogel material according to claim 1, characterized in that: The solvent is a mixed solvent of water and glycerol.

3. The method for preparing a programmable self-dissolving hydrogel material according to claim 1, characterized in that: The photocuring method is: placing the hydrogel precursor liquid in a mold under 365 nm ultraviolet light for 60 to 300 seconds to cure it into a hydrogel material, or using photocuring 3D printing technology to print it into a three-dimensional structure.

Citation Information

Patent Citations

  • Cross-linking agent for degradable hydrogel, degradable polyacrylamide hydrogel based on cross-linking agent as well as preparation method and application of degradable polyacrylamide hydrogel

    CN115109201A

  • Self-assembly gel preparation capable of treating traumatic brain injury as well as preparation method and application of self-assembly gel preparation

    CN117562854A

  • Universal cross-linking agent capable of being oxidized, reduced and degraded, hydrogel as well as preparation and application of universal cross-linking agent

    CN118063366A